Aldosterone and cortisol affect the risk of sudden cardiac death in haemodialysis patients - Drechsler, Christiane; Ritz, Eberhard; Tomaschitz, Andreas; Pilz, Stefan; Schönfeld, Stephan; Blouin, Katja; Bidlingmaier, Martin; Hammer, Fabian; Krane, Vera; März, Winfried; Allolio, Bruno; Faßnacht, Martin; et al. (European heart journal, 2013)
Sudden cardiac death is common and accounts largely for the excess mortality of patients on maintenance dialysis. It is unknown whether aldosterone and cortisol increase the incidence of sudden cardiac death in dialysis patients.We analysed data from 1255 diabetic haemodialysis patients participating in the German Diabetes and Dialysis Study (4D Study). Categories of aldosterone and cortisol were determined at baseline and patients were followed for a median of 4 years. By Cox regression analyses, hazard ratios (HRs) were determined for the effect of aldosterone, cortisol, and their combination on sudden death and other adjudicated cardiovascular outcomes. The mean age of the patients was 66 ± 8 years (54% male). Median aldosterone was <15 pg/mL (detection limit) and cortisol 16.8 µg/dL. Patients with aldosterone levels >200 pg/mL had a significantly higher risk of sudden death (HR: 1.69; 95% CI: 1.06-2.69) compared with those with an aldosterone <15 pg/mL. The combined presence of high aldosterone (>200 pg/mL) and high cortisol (>21.1 µg/dL) levels increased the risk of sudden death in striking contrast to patients with low aldosterone (<15 pg/mL) and low cortisol (<13.2 µg/dL) levels (HR: 2.86, 95% CI: 1.32-6.21). Furthermore, all-cause mortality was significantly increased in the patients with high levels of both hormones (HR: 1.62, 95% CI: 1.01-2.62).The joint presence of high aldosterone and high cortisol levels is strongly associated with sudden cardiac death as well as all-cause mortality in haemodialysed type 2 diabetic patients. Whether a blockade of the mineralocorticoid receptor decreases the risk of sudden death in these patients must be examined in future trials.
online publish-ahead-of-print 4 December 2012
Gesehen am 18.12.2020